A Cross-Cultural Comparison of Government Influence on Collaborative Watershed Institutions in Ohio (USA) and the Dominican Republic and Implications for Decentralization of Resource Management. Issue 10 (3rd October 2021) - Bonnell, Joseph E.; Koontz, Tomas M.
Abstract: Collaborative watershed institutions (CWIs) have been promoted as effective vehicles for facilitating decentralization and collaboration between government and local stakeholders in both developed and less developed nations. While governmental actors may see CWIs as a means to increase stakeholder participation, they may also use a variety of mechanisms to influence these institutions to advance agency policies. This article describes the authors' experiences with CWIs in two very different contexts: the state of Ohio (USA) and the Caribbean nation of the Dominican Republic. Using the Government Impacts Framework, the authors identify mechanisms by which government institutions influence CWI form and function. The degree and nature of impacts of governmental influence varies across CWIs, but, in general, CWIs that are closely aligned with government agency priorities experience fewer and less disruptive impacts. This influence can, in some instances, hinder efforts to decentralize water resource management, and instead reinforce existing centralized power structures.